Manajemen Rantai Pasok Bakso Ikan Swanggi Di PT ILM - Selvi Sukma Ayu; Prayoto; Dimas Bayu Sasongko (Badan Penerbitan Fakultas Pertanian Universitas Ratu Samban, 2025)
Supply chain management is an important aspect in the success of a company, including in the food industry such as swanggi fishballs. This study aims to analyze the main components in PT. ILM's supply chain management, which includes the flow of raw material receipts, production processes, marketing, shipping and consumers. In this context, loyal consumers are the main focus, where consumer satisfaction plays an important role in increasing the company's revenue. The company has expanded its marketing reach to various cities in Indonesia with a segmented marketing strategy, which allows for adjustments to specific customer needs. The flow of information in this supply chain consists of two directions, namely from upstream to downstream and vice versa, which includes products, information, and finance. This study is expected to provide deeper insight into supply chain management in the fishball industry.